A Low-Profile Magneto-Electric Dipole Antenna with Wideband Characteristics - Wang, Heesu; Park, Ikmo (ISAP 2024 - International Symposium on Antennas and Propagation, 2024)
This study developed a small, low-profile magneto-electric dipole antenna with wideband characteristics by adding a capacitively loaded loop (CLL) structure and stubs. The proposed antenna consists of an electric dipole, a magnetic dipole, and a reflector. The folded reflector and bent electric dipole that constitute the antenna operate as a CLL at low frequencies, thereby substantially reducing the electrical size of the antenna. The rectangular stubs attached to the electric dipole compress the higher-order modes of the dipole, expanding the bandwidth of the antenna. The electrical size of the proposed antenna is 0.316 × 0.292 × 0.0389 λL3, its -10 dB impedance bandwidth is 0.73 to 1.97 GHz (91.9%), and the gain achieved within the operating bandwidth is 4.3 to 6.7 dBi.
Keywords: Capacitively loaded loops; Electric dipole; Loop structure; Low-profile; Lower frequencies; Magneto-electric dipole antennas; Magneto-electric dipoles; Miniaturized antennas; Wideband antenna; Wideband characteristics; capacitively loaded loop; low-profile; magneto-electric dipole; miniaturized antenna; wideband antenna